2007
DOI: 10.1111/j.1539-6924.2007.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Efficiency of Controlling Campylobacter on Broiler Chicken Meat

Abstract: Campylobacter bacteria are an important cause of foodborne infections. We estimated the potential costs and benefits of a large number of possible interventions to decrease human exposure to Campylobacter by consumption of chicken meat, which accounts for 20-40% of all cases of human campylobacteriosis in the Netherlands. For this purpose, a farm-to-fork risk assessment model was combined with economic analysis and epidemiological data. Reduction of contamination at broiler farms could be efficient in theory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(29 citation statements)
references
References 23 publications
(37 reference statements)
2
27
0
Order By: Relevance
“…Campylobacter counts in chicken feces were comparable at both sampling dates (5 log 10 colony-forming units (CFU) per gram), despite on-farm pathogen reduction efforts introduced during this period. This concurs with the findings of the CARMA project that, although theoretically possible, attaining Campylobacter-free birds is unrealistic in the short-term (Havelaar et al 2007). In contrast, the levels of Campylobacter on broiler carcasses exiting the chiller in 2001 (3.03 log 10 CFU/g) were 1 log lower than 1995 estimates (4.11 log 10 CFU/g), indicating the effectiveness of HACCP interventions during processing (Stern and Robach 2003).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Campylobacter counts in chicken feces were comparable at both sampling dates (5 log 10 colony-forming units (CFU) per gram), despite on-farm pathogen reduction efforts introduced during this period. This concurs with the findings of the CARMA project that, although theoretically possible, attaining Campylobacter-free birds is unrealistic in the short-term (Havelaar et al 2007). In contrast, the levels of Campylobacter on broiler carcasses exiting the chiller in 2001 (3.03 log 10 CFU/g) were 1 log lower than 1995 estimates (4.11 log 10 CFU/g), indicating the effectiveness of HACCP interventions during processing (Stern and Robach 2003).…”
Section: Introductionsupporting
confidence: 89%
“…The Dutch Campylobacter Risk Management and Assessment (CARMA) project appraises the cost of campylobacteriosis at 21 million Euros annually with 20-40% of cases attributed to contaminated poultry (Havelaar et al 2007). In the United States, foodborne campylobacteriosis follows infection with C. jejuni (∼90% of cases) and Campylobacter coli (∼5% of cases) together causing two million human cases accounting for ∼$1.2 billion in productivity losses annually (Buzby and Roberts 1997;http://www.ers.usda.…”
Section: Introductionmentioning
confidence: 99%
“…There has been evidence reported that irradiation and chemical wash were effective in minimising Campylobacter on chicken meat. For example, irradiation can reduce Campylobacter by 20.8 log (cfu/carcass), (Havelaar et al., 2007) and chemical wash (e.g. application of chlorine in spin chillers at 35 ppm) has been a major tool in reducing human campylobacteriosis in New Zealand (New Zealand Food Safety Authority, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation into vaccination of chickens provided evidence of inconsistent success in reducing Campylobacter (Hermans et al., 2011). Better on-farm hygiene practices have been reported to lower the risk of Campylobacter colonisation by 95% (Havelaar et al., 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation